The Power of Mediator Suggestions in Mediating the Settlement of Pancasila Industrial Relations Disputes Outside the Court - Siti Kunarti (Jurnal Dinamika Hukum, 2019)
One of the settlements of disputes outside the court, mediation is understood as a settlement that is non-judgmental, fast, inexpensive, and provides access to the disputing parties to obtain justice or a satisfactory settlement by means of a win-win solution. The role of an industrial relations mediator is urgently needed to achieve harmonious industrial relations. The mediator becomes a point of contact who plays an active role in settlements outside the court. The strength of the mediator's suggestion in mediation is something that greatly determines the continuity of the settlement process because it can be a dispute resolution up to the Industrial Relations Court (PHI) if the negotiation and the mediator's written recommendation are not accepted by one or both parties. In a formal claim to the Industrial Relations court, a written recommendation is part of the minutes of industrial relations dispute settlement. A written recommendation only has power if a collective agreement is made and is registered with the PHI to get the power to be implemented. Deliberation to reach a consensus through mediation settlement with a written suggestion as one of the settlement methods in Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement has not been optimally implemented as long as it is not registered with PHI to have permanent legal force.Keywords: Mediation; Pancasila; Industrial Relations Disputes.